Pengaruh Fasilitas Kerja Dan Stres Kerja Terhadap Produktivitas Karyawan Pada PT Bfi Finance Tbk Area Cisauk Kab - Tangerang - Andri Pramana Putra, Muhamad; Bakar Dja'far, Abu (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. This studyaims to determine the effect of Work Facilities and Work Stress, both partiallyand simultaneously, on employee productivity at PT. BFIFinance Tbk, Cisauk area, Tangerang Regency. This research isassociative causal research with a quantitative approach. The techniqueused in sampling was non-probabilitysampling of employees at PT. BFI Finance Tbk, Cisauk area, Tangerang Regencywith a total sample of 60 employees and the instrument used was aquestionnaire. The data analysis technique used was multiple linear regression analysis. Based on the test results, it was found that: 1) Work facilitieshave a significant partial effect on employee productivity,as indicated by the significance value (0.003 < 0.05) and thecalculated t-value> ttable (3.154 > 1.671); 2) Work stress has asignificant partial effect on employee productivity, as indicatedby the significance value (0.001 < 0.05) and tcount value <ttable ( 4.250 > 1.671); 3) Work facilities and work stresstogether (simultaneously) have a significant effect on employee productivitywith a significance value (0.001 > 0.05). The results of the multiple linear regression analysisyielded a regression equation of Y = 10.204 + 0.55x1 +0.426x2 Work Facilities 0.599 Work Stress, which means that work facilitieshave a positive effect while work stress has a negative effecton employee productivity. This study also shows that the coefficient of determination (R2) obtained is 0.302 or 30.2%of employee productivity can be explained based on work facilities and work stressexperienced by employees, while the remaining 69.8% is explainedby other factors not examined in this study. Keywords: Workplace Facilities, Work Stress, and Productivity Keywords: Work Facilities, Work Stress, and Productivity